Meta-data analysis of kidney stone disease highlights ATP1A1 involvement in renal crystal formation - Yang Li; Xiuli Lu; Zhihao Yu; Haozhen Wang; Bing Gao (Redox Biology, 2023)
Nephrolithiasis is a complicated disease affected by various environmental and genetic factors. Crystal-cell adhesion is a critical initiation process during kidney stone formation. However, genes regulated by environmental and genetic factors in this process remain unclear. In the present study, we integrated the gene expression profile data and the whole-exome sequencing data of patients with calcium stones, and found that ATP1A1 might be a key susceptibility gene involved in calcium stone formation. The study showed that the T-allele of rs11540947 in the 5′-untranslated region of ATP1A1 was associated with a higher risk of nephrolithiasis and lower activity of a promoter of ATP1A1. Calcium oxalate crystal deposition decreased ATP1A1 expression in vitro and in vivo and was accompanied by the activation of the ATP1A1/Src/ROS/p38/JNK/NF-κB signaling pathway. However, the overexpression of ATP1A1 or treatment with pNaKtide, a specific inhibitor of the ATP1A1/Src complex, inhibited the ATP1A1/Src signal system and alleviated oxidative stress, inflammatory responses, apoptosis, crystal-cell adhesion, and stone formation. Moreover, the DNA methyltransferase inhibitor 5-aza-2′-deoxycytidine reversed ATP1A1 down-regulation induced by crystal deposition. In conclusion, this is the first study to show that ATP1A1, a gene modulated by environmental factors and genetic variations, plays an important role in renal crystal formation, suggesting that ATP1A1 may be a potential therapeutic target for treating calcium stones.